Perbedaan Produksi TBS dan Penjualan CPO Sebelum dan Sesudah Pandemi Covid-19 - Hasanul Arifin Daulay (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2023)
Covid-19 has made almost all sectors affected by this pandemic, not only the health sector, the economic sector has also experienced some serious impacts due to the Covid-19 pandemic. The impact of the Covid-19 pandemic is felt by 12.15 million people who work in the informal sector. This group is the most vulnerable to poverty affected by Covid-19. One of the companies affected during the Covid-19 pandemic is oil palm plantations. Based on observations in 2020, the lockdown of China to India made CPO prices rise by almost 4%, where CPO prices strengthened by 3.91% to RM 2,378 / ton. While in 2022 the price of Crude Palm Oil (CPO) fell quite sharply, where the price of CPO on the Malaysian Exchange was recorded at MYR 6,649 / ton and fell by 2.34%. The Covid-19 pandemic threatens the price of CPO to plunge further, this makes the apocalypse of CPO (Fresh Fruit Bunches) prices even closer after the implementation of the domestic market obligation (DMO) policy with adjusted prices or domestic price obligation (DPO) for palm oil. FFB production at PT Perkebunan Nusantara II in the Bandar Klippa Plantation in 2020 decreased by 18,323.37 tons with a decrease in growth of -0.65%.